Understanding Social Studies Concepts through Circuit Learning Models and Creative Problem-Solving Models in Fifth Graders - Wijaya, Heri Agus; Usman, Herlina; Pratiwi, Ayu Diah; Alawiah, Tuti (EduBasic Journal: Jurnal Pendidikan Dasar, 2023)
This study aimed to determine the development of social studies learning concepts between students who use the circuit learning model and students who use the Circuit Learning model process using the Creative Problem-Solving method in fifth-grade social studies learning in the 2022- 2023 academic year. This research uses a quasi-experimental method and the results of the ability to understand the concept of social studies data collected through a test description or essay. To analyze the differences between those two learning methods, the t-test with a significant level of 0.05 (5%) was used. After being taught using the Circuit Learning model and Creative Problem-Solving models, the results of the ability to understand the concept of social studies have a difference. Students who use the circuit learning model get an average score of 82.1, while students who use the problem-solving method get an average score of 72.86. Based on the results of the analysis of hypothesis test data using the t-test at a significant level of 0.05 (5%) obtained tcount ttable is 3.80 1.686 so H1 is accepted and H0 is rejected. Students who use the circuit learning model have a better understanding of social studies concepts than those who use the creative problem-solving model. They are more confident in learning, making it easier for them to understand social studies concepts because they learn collaboratively and competitively and are responsible for their responsibilities in the group.